Numerical investigation of the influence of sphere voids on the flexural performance of square RC voided slab-beam system - Nareshnayak, Nunavath (Journal of Structural Engineering, 2024)
This paper presents a numerical approach to evaluate the ultimate load and the flexural behavior of the two-way sphere voided slab-beam systems with various layouts of sphere voids. The slab is the most widely used structural element, used in framed and regular load-bearing masonry constructions. A voided slab is a reinforced concrete slab in which void shapers are placed between the top and bottom reinforcing bars before the concrete is poured to reduce the slab’s self-weight. The developed model was validated with prior experimental work available in the literature. The reinforced concrete model was created using nonlinear stress-strain relationships of concrete and reinforcing steel. The flexural capacity of the sphere voided slab-beam was determined in the numerical model, and later its structural parameters were compared with the control model. Numerical results indicate that the change in the load taken by the sphere voided slab-beam model is 12.6% more than that of the control model. It is because of the 10% reduction in the self-weight of the sphere voided model than the control model. A parametric analysis was conducted to study the impacts of spherical balls with various configurations on flexural capacity. The slab-beam model’s lowest ultimate load is observed in the three rows of sphere voids provided in only one direction case (X-3 row SV model). The slab-beam model has the highest flexural load in the three rows of sphere voids provided in both directions case (X and Y-3 row SV model). The deflection contour of the X and Y-3 row SV model differs from the X-3 row SV model. At 100 mm deflection in the slab, the beam deflection of the X-3 row SV model is 11.27 mm, while the beam deflection of the X and Y-3 row model is 17.88 mm. The arrangement of voids inside the slab influences flexural parameters like initial cracking load, rebar stress and deflection contour.